Derecho humano al agua y control de convencionalidad - Martínez, Adriana N. (2013)
Humanity faces the challenge of achieving the sustainability of water resources supply for the satisfaction of human needs and ofensuring the sustainability of the natural ecosystems for the achievement of sustainable human development and the quality of life of present and future generations. For this reason the recognition of access to water as a Human Right has fundamental significance. We proceed to analyze the international instruments that provide content and legal basis to the human right to water and the obligations of States. In this context, we deal with the constitutional reception of human right to water in Argentina in the constitutional reform of 1994 and the control of conventionality as guarantor of access to water, which has led to different domestic courts to consider cases in which a violation ofthe right to water was proved.